Investigating English as a Second Language (ESL) Learners’ Writing Skills through Open-source Software: A Case Study - Shruthi, Subramanian; Aravind, Banumathi Rajamanickam (Tecno Scientifica Publisher, 2024)
The purpose of this study was to investigate the feedback of English as a Second Language (ESL) learners on their writing skills, with a focus on exploring ESL students' progress in writing skills based on tenses through open-source software. The software is employed to assess each student's improvement. This research follows a qualitative method, and data were collected through semi-structured interviews and the think-aloud protocol. The results are categorized into four main areas: (a) Feedback provided by students; (b) Students' perception of tenses and writing skills; (c) Students' views on teachers' teaching; and (d) practice through open-source software. The study revealed that ESL students had a positive perception of tenses, and their writing skills were enhanced by the semi-structured interviews conducted by ESL learners. The conclusion of the study highlighted that students themselves could recognize improvements in their syntax errors and sentence formation, with very few exceptions. It is advisable for teachers to incorporate a variety of proper grammatical topics in the future to assist students in improving their writing abilities.